The Influence of Customer Testimonials and Product Quality on Purchasing Decisions in MSMEs in Pancasila Field, Palopo City - Nur Azizah; Muammar Khaddapi; Muhammad Aqsa (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of customer testimonials and product quality on purchasing decisions of Micro, Small, and Medium Enterprises (MSMEs) in the Pancasila Field area, Palopo City. This study uses a quantitative approach with a purposive sampling method. The sample consists of 100 respondents who are consumers of various MSMEs in the area. Data collection was carried out by distributing questionnaires, while the data analysis technique used the help of SPSS version 26 software. The independent variables in this study are customer testimonials and product quality, while the dependent variable is purchasing decisions. The results of the analysis show that both customer testimonials and product quality have a positive and significant effect partially on purchasing decisions. In addition, simultaneously, both variables also have a significant effect on increasing purchasing decisions. These findings indicate that customer experience-based marketing strategies and improving product quality can be key factors in driving consumer decisions to purchase. Therefore, MSMEs are advised to pay more attention to product quality and utilize customer testimonials as an effective promotional tool.